The genus Phanagenia Banks, 1933 (Hymenoptera: Pompilidae) from China with descriptions of two new species and a key to the world species - He, Yi; Li, Qiang; Ma, Li (Zootaxa, 2024)
The genus Phanagenia Banks, 1933 from China is reviewed. Two new species, Phanagenia bidenticulata He & Ma, sp. nov. from the Oriental region (Yunnan) and Ph. cornuta He & Ma, sp. nov. from the Palaearctic region (Hebei and Inner-Mongolia), are described and illustrated from China. The genus Phanagenia and the species Ph. takasago Tsuneki, 1989 is newly recorded from the Palaearctic region. A key to the world species of the genus Phanagenia is given.